2010
DOI: 10.1044/1092-4388(2009/08-0254)
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Density and Word Frequency Predict Vocabulary Size in Toddlers

Abstract: Children at the lowest points of a continuum of vocabulary size may be extracting statistical properties of the input language in a manner quite different from their more able age peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
130
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(150 citation statements)
references
References 33 publications
15
130
2
3
Order By: Relevance
“…Many studies have found positive correlations (around r = .6 -.8) between such holistic assessment by human raters and text length (e.g., Grandin & Lindskog, 2007;Jafarpur, 1991;Löfqvist, 1990). It is also a common finding that older 8 children produce longer texts than younger children (e.g., Asker-Árnason et al, 2008;2010) and that children with typical language development produce longer texts than children in clinical groups (e.g., Reuterskiöld Wagner et al, 1999). McFadden & Gillam (1996) studied teachers' assessments of overall quality of written as well as spoken narratives from different groups of children.…”
Section: Vocabulary Development and Narrativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have found positive correlations (around r = .6 -.8) between such holistic assessment by human raters and text length (e.g., Grandin & Lindskog, 2007;Jafarpur, 1991;Löfqvist, 1990). It is also a common finding that older 8 children produce longer texts than younger children (e.g., Asker-Árnason et al, 2008;2010) and that children with typical language development produce longer texts than children in clinical groups (e.g., Reuterskiöld Wagner et al, 1999). McFadden & Gillam (1996) studied teachers' assessments of overall quality of written as well as spoken narratives from different groups of children.…”
Section: Vocabulary Development and Narrativesmentioning
confidence: 99%
“…For example, one would expect to find puppy close to dog but far from puppet (which, on the other hand, is a phonological neighbour; Stokes, 2010). Documents can be compared in the semantic space following an aggregation of all semantic representations related to the words in the document.…”
Section: Semantic Spacesmentioning
confidence: 99%
“…In reality, however, the two must be intertwined: a processing episode with a word will be influenced by an individual's previous experiences with that word; in turn, the episode will provide a new encounter to add to the accumulated knowledge the individual has of that word, and so influence future processing. Differences in vocabulary size early in development matter as this will influence the statistical properties that are extracted from the input (see [73] for evidence) and in turn, this will serve to influence subsequent learning and processing.…”
Section: Linking Lexical Learning and Lexical Processingmentioning
confidence: 99%
“…In speech production, many studies have shown evidence for hyperarticulation in high ND words (Munson & Solomon, 2004;Scarborough, 2004;Wright, 2004), which has been interpreted in support of a listener-oriented view of phonetic reduction. Other studies have shown how ND may be useful in characterizing word learning: children's lexicons tend to contain more high ND words at first, and over time expand to low ND words (Coady & Aslin, 2003;Stokes, 2010). In short, the concept of ND is applicable to a wide range of questions in language processing and acquisition.…”
Section: Introductionmentioning
confidence: 99%